2018
DOI: 10.48550/arxiv.1812.04563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equivalences of (co)module algebra structures over Hopf algebras

Abstract: We introduce the notion of support equivalence for (co)module algebras (over Hopf algebras), which generalizes in a natural way (weak) equivalence of gradings. We show that for each equivalence class of (co)module algebra structures on a given algebra A, there exists a unique universal Hopf algebra H together with an H-(co)module structure on A such that any other equivalent (co)module algebra structure on A factors through the action of H. We study support equivalence and the universal Hopf algebras mentioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…We shall recall the construction and the main properties of the quantum symmetry semigroup of a finite dimensional algebra A. The results below in this sections are well-known or have been recently proven in much more general cases [3,4]. The following is [18, Theorem 1.1]: we shall present a short proof since we prefer to give an explicit construction of the algebra a(A), using generators and relations implemented by the structure constants of A in the spirit of […”
Section: Preliminariesmentioning
confidence: 99%
“…We shall recall the construction and the main properties of the quantum symmetry semigroup of a finite dimensional algebra A. The results below in this sections are well-known or have been recently proven in much more general cases [3,4]. The following is [18, Theorem 1.1]: we shall present a short proof since we prefer to give an explicit construction of the algebra a(A), using generators and relations implemented by the structure constants of A in the spirit of […”
Section: Preliminariesmentioning
confidence: 99%
“…[5].) As the authors showed in [2], this notion can be generalized further to the case of (co)module structures on algebras. Equivalence of (co)module structures can be used, for instance, in the study of polynomial H-identities.…”
Section: Introductionmentioning
confidence: 97%
“…To start with, in the 1960s, M. E. Sweedler introduced the universal measuring coalgebra which lead to the notion of the universal measuring bialgebra [11,Chapter VII]. Unlike the universal Hopf algebra/bialgebra of a specific action defined in [2], Sweedler's universal measuring bialgebra is universal among all actions, not necessarily equivalent to a given one. Moreover, Sweedler's construction leads naturally to the notion of a universal acting Hopf algebra of an algebra (see Example 4.4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both objects are very important: as explain in [19], the Hopf envelope of a(A, A) plays the role of a symmetry group in non-commutative geometry. For further details we refer to [1,2,3]. A more general construction, which contains all the above as special cases, was recently considered in [4] in the context of Ω-algebras.…”
Section: Introductionmentioning
confidence: 99%